공정성에 대한 인식이 사회갈등 수준에 미치는 영향 : 신뢰와 소통의 매개효과를 중심으로 - 임동진; Dong-jin Lim; 박관태; Kwan-tae Park (한국행정연구, 2017)
본 연구의 목적은 우리사회의 공정성에 대한 인식이 사회갈등 수준에 어떠한 영향을 미치는지와 신뢰와 소통이 매개요인의 역할을 할 수 있는지를 분석하고 이를 토대로 이론적ㆍ정책적 함의를 제시하는 것이다. 이를 위해 2016년 우리나라 일반 국민 8,000명을 대상으로 한 설문조사 자료를 활용하였다. 본 연구의 연구결과를 요약하면 다음과 같다. 첫째, 우리사회의 전반적인 공정성과 사회갈등에 대한 설문조사 결과, 우리국민들은 공정성은 2.12(4점 척도)로 우리사회가 공정하지 않고, 사회갈등은 2.96으로 우리사회의 갈등이 심각하다고 인식하였다. 둘째, 우리사회의 공정성에 대한 인식이 신뢰요인(개인신뢰, 기관신뢰)과 소통요인(개인소통)에 미치는 영향을 분석한 결과, 공정성 인식은 신뢰요인과 소통요인에 정(+)의 영향을 미치는 것으로 나타났다. 이는 우리국민들은 우리사회가 공정할수록 신뢰와 소통이 증가할 것으로 인식한다는 것이다. 셋째, 우리사회 갈등 수준(강도)에 영향을 미치는 요인은 공정성이(Beta=-0.346) 가장 높고, 그 다음으로 기관신뢰 (Beta=-0.099), 개인소통(Beta=-0.014)의 순으로 나타났다. 마지막으로, 공정성, 신뢰와 소통의 총효과 및 매개효과 분석 결과, 공정성이 사회갈등 수준에 미치는 총 효과는 -0.279(직접효과=-0.240, 간접효과=-0.038), 기관신뢰가 사회갈등 수준에 미치는 총 효과는 -0.076로 나타났고, 공정성과 사회갈등 간 관계에서 기관신뢰의 매개효과는 -0.052로 나타났다. 이는 기관신뢰가 공정성과 사회갈등 간 관계에서 매개요인 역할을 함으로써 사회갈등 수준을 감소시키고 있음을 보여주는 것이다. The purpose of this study is to analyze the degree to which justice influences the level of social conflicts and the mediating effects of trust and communication, and to suggest the theoretical and policy implications in Korea. To do this, the paper utilizes the survey data targeting 8,000 general public living in South Korea as of 2016. The summaries of this paper are as follows. First, as the results of the analysis on the general perceived level of justice and social conflict in Korean society, most of Korean perceive that the society is not just(2.12 in Likert 4-point scale), and social conflict is very serious(2.96). Second, it is found that the perception of justice has a positive relationship with trust factors and communication factors. So to speak, the more the public recognize that the society is more just, the more people believe that trust and communication are increased. Third, with regard to the factors which influence the level of social conflicts, justice(Beta=-0.346) is the most important, Next is the institutional trust(Beta=-0.099), personal communication(Beta=-0.014) in order. Finally, the total effects that justice influences the level of social conflicts is -0.279 (including direct effect=-0.240, indirect effect=-0.038), while the total effect that the institutional trust has an influence on the degree of social conflicts is -0.076. The mediating effect of the institutional trust on the relationship between justice and social conflicts is -0.052. These results mean that the institutional trust has the mediating role on the relations between justice and social conflicts and decreasing the level of social conflicts.